LONG AND WEIGHT RELATIONSHIP TO FECUNDITY OF CEMPEDIK FISH (Osteochilus spilurus) IN CATCHING SEASON IN THE LENGGANG RIVER, EAST BELITUNG - ardiansyah kurniawan; Neri Rizkika; Yulian Fakhrurrozi (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
The one of Belitung Island’s native fish which has important economic value is Cempedik fish (Osteochilus spilurus). Its consumption, which still relies on natural catchments, requires a study of its biology and ecology. One of the studies that have never been studied in the maturity of this species is the relationship of fecundity with fish weight - length and gonad weight. This study used samples of Cempedik fish from the Lenggang River, East Belitung which were obtained randomly from the catches of fishermen. Sampling adjusts the fishing season that occurs in the rainy season. The preparation was carried out on whole fish using 4% formalin. Calculation of fecundity gravimetrically and compared with fish lengths and gonad weights in the graph. Fecundity in 2015 was 222 – 10,947 eggs and in 2016 there were 335 – 2,060 eggs. Fish body length and weight affected the fecundity of the 2015 fish sample but had no effect on the 2016 sample. This is predicted to occur due to differences in sampling time to position and rainfall in the rainy season, availability and suitability of natural feed, and changes in habitat quality. Gonadal weight correlated with fecundity, where the higher the gonadal weight, the higher the fecundity. Keywords: Cempedik, rainy season, maturity, fecundity.